2019
DOI: 10.1002/cam4.2439
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐institutional analysis of the prognostic significance of postoperative complications after curative resection for gastric cancer

Abstract: Background Insufficient data are available on the prognostic significance of complications after resection of gastric cancer. Therefore, we aimed to assess this gap in our knowledge by studying patients with resectable gastric cancer. Methods A multi‐institutional retrospective database comprising clinical information of 3575 patients who received resection of gastric cancer from 2010 to 2014 at nine institutions. Grades 2 or greater complications of the Clavien‐Dindo c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…These complications can impede recovery, delay the initiation of adjuvant chemotherapy, and compromise quality of life [1,2]. Moreover, postoperative complications have been shown to adversely affect the overall and recurrence-free survival of patients after curative gastrectomy for gastric cancer; thus, some complications can be catastrophic for both short-and longterm outcomes [3][4][5]. The recently reported overall morbidity rates after resection for gastric cancer are 17.4-24.5% in East Asia and a slightly higher rate of 13.6-46% in Western countries [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These complications can impede recovery, delay the initiation of adjuvant chemotherapy, and compromise quality of life [1,2]. Moreover, postoperative complications have been shown to adversely affect the overall and recurrence-free survival of patients after curative gastrectomy for gastric cancer; thus, some complications can be catastrophic for both short-and longterm outcomes [3][4][5]. The recently reported overall morbidity rates after resection for gastric cancer are 17.4-24.5% in East Asia and a slightly higher rate of 13.6-46% in Western countries [2,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, oncological outcomes were comparable between the two groups. A previous study indicates that postoperative complications have less adverse impact on prognosis of patients who underwent distal gastrectomy than those who underwent total gastrectomy [17].…”
Section: Discussionmentioning
confidence: 94%
“…We have recently reported that postoperative complications and delay in postoperative adjuvant chemotherapy adversely affected the prognosis in patients with gastric cancer [15,17]. In this study, we compared survivals between the R-Y and B-I groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, perioperative complications have been shown to be strongly associated with impaired long-term outcomes[ 26 , 27 ]. This could be the result of either delayed adjuvant chemoradiation or no adjuvant chemoradiation in complicated cases[ 28 ]. Moreover, ERAS protocols can bring potential benefits to advanced gastric cancer that may be related to a lower stress response and reduction in insulin resistance, which are considered to be factors associated with a good cancer long-term prognosis[ 29 - 31 ].…”
Section: Discussionmentioning
confidence: 99%